KAJIAN BENTUK PERTUNJUKAN GRUP MUSIK ANGKLUNG KRIDOTOMO DI YOGYAKARTA (Jurnal Seni Musik, 2016)
The purpose of this study is to investigate and describe perfomance form of music group Angklung Kridotomo. Research methods applied in this study is qualitative descriptive. The result showed, music group Angklung Kridotomo do perfomance in Beringharjo market at day and in Malioboro street at night. Angklung Kridotomo group perfomance consisted by opening session that contain greeting and play opening music, at the prime session playing pop, campursari, and dangdut music. At the last session playing requested song and ended with closing